Combined stratigraphic-structural play characterization in hydrocarbon exploration: A case study of Middle Miocene sandstones, Gulf of Suez basin, Egypt - Radwan, Ahmed. E.; Rohais, Sébastien; Chiarella, Domenico (Journal of Asian earth sciences, 2021)
[Display omitted] •Combined stratigraphic-structural trap potentiality.•Multi dataset as successful exploration approach.•Gulf of Suez exploration potentiality.•Hydrocarbon potentiality in the middle Miocene Baba sandstones. As most hydrocarbon discoveries in the Gulf of Suez basin are in structural traps, little research has focused on the evaluation of stratigraphic or combined play in the region. The Badri field represents one of the most prolific oil and gas fields in the Gulf of Suez basin with a large cumulative production from the Miocene Belayim and Kareem Reservoirs. However, Middle Miocene Baba sandstones is still relatively underexplored when compared to other prolific producing reservoir intervals. Recent drilling data from the Badri field has renewed interest in this Member as a reservoir unit due to the lateral facies variations from shale to sandstones recognized in some wells. This study aims to investigate the structural and stratigraphic characterization and hydrocarbon potentiality of Serravalian Baba sandstones. An integrated mineralogical, sedimentological, petrophysical, and reservoir characterization analysis was conducted to obtain and evaluate information about the main reservoir characteristics of Baba sandstones using thin sections, wireline logs (i.e. Resistivity, Density-Neutron, Gamma-ray, and Sonic), and subsurface geologic mapping. Results support that Baba sandstones interval has good reservoir properties and high potentiality to produce hydrocarbon increasing the reserves in the studied area. Moreover, the entrapment style of Baba sandstones interval is due to the combined effect of stratigraphic and structural components. Accordingly, this study recommends more attention for the stratigraphic and combined stratigraphic-structural traps present along the Gulf of Suez basin.